Biological properties of soils of former forest fires in Samosir Regency of North Sumatera - D Elfiati; D Delvian (Journal of Degraded and Mining Lands Management, 2016)
A study that was aimed to identify the impact of forest fires on the biological properties of soils was carried out at former forest fire areas in Samosir Regency of North Sumatera. Soil samples were collected from former forest fire areas of 2014, 2013, 2012, 2011, 2010. The composite soil samples were collected systematically using diagonal method as much as 5 points in each period of fire. The soil samples were taken at three plots measuring 20 x 20 m 0-20 cm depth. Soil biological properties observed were soil organic C content, total number of microbes, abundance of arbuscular mycorrhizal fungi, phosphate solubilizing microbes, and soil microbial activity. The results showed that organic C content ranged from 0.75 to 2.47% which included criteria for very low to moderate. Arbuscular mycorrhizal fungi spores were found belonging to the genus of Glomus and Acaulospora. Spore number increased with the fire period ranging from 45 spores (forest fire in 2014) to 152 spores (forest fire in 2010). The total number of microbes obtained ranged from 53.78 x 107 cfu/mL (forest fire in 2010) to 89.70 x107 cfu/mL (forest fire in 2013). It was found 29 isolates of phosphate solubilizing microbes that consisted of 14 bacterial isolates and 15 fungi isolates with densities ranging from 27.642 x105 cfu/mL (forest fires in 2014) to 97.776 x 105 cfu/ mL (forest fires in 2011). The isolates of phosphate solubilizing bacteria identified consisted of Pseudomonas, Flavobacterium, Staphylococcus, and Mycobacterium genus, whereas the isolates of phosphate solubilizing fungi obtained consisted of Aspergillus and Penicillium genus. Soil respiration ranged from 2.14 kg / day (forest fire in 2010) up to 3.71 kg / day (forest fire in 2013). The varied results were greatly influenced by the type or form of the fires and intensity of fires. In the study area the type or form of the fires were canopy fires with low intensity.